Quality of life and depression 3 months after intracerebral hemorrhage - Sallinen, Hanne (Brain Behav, 2019)
OBJECTIVES: Quality of life (QoL) after intracerebral hemorrhage (ICH) is poorly known. This study investigated factors affecting QoL and depression after spontaneous ICH. MATERIALS AND METHODS: This prospective study included patients admitted to Helsinki University Hospital between May 2014 and December 2016. Health‐related QoL (HRQoL) at 3 months after ICH was measured using the European Quality of Life Scale (EQ‐5D‐5L), and the 15D scale. Logistic regression analyses were used to test factors affecting HRQoL. EQ‐5D‐5L anxiety/depression dimension was used to analyze factors associated with anxiety/depression. RESULTS: Of 277 patients, 220 were alive, and sent QoL questionnaire. The questionnaire was returned by 124 patients. Nonreturners had more severe strokes with admission National Institutes of Health Stroke Scale (NIHSS) 7.8 (IQR 3.0–14.8) versus 5.0 (IQR 2.3–11.0); p = 0.018, and worse outcome assessed as modified Rankin Scale 3–5 at 3 months 59.4% versus 44.4% (p = 0.030). Predictors for lower HRQoL by both scales were higher NIHSS with OR 1.28 (95% CI 1.13–1.46) for EQ‐5D‐5L, and OR 1.28 (1.15–1.44) for 15D, older age (OR 1.10 [1.03–1.16], and OR 1.09 [1.03–1.15]), and chronic heart failure (OR 18.12 [1.73–189.27], and OR 12.84 [1.31–126.32]), respectively. Feeling sad/depressed for more than 2 weeks during the year prior to ICH was predictor for lower EQ‐5D‐5L (OR 10.64 [2.39–47.28]), and history of ICH for lower 15D utility indexes (OR 11.85 [1.01–138.90]). Prior feelings of sadness/depression were associated with depression/anxiety at 3 months after ICH with OR 3.62 (1.14–11.45). CONCLUSIONS: In this cohort of ICH patients with milder deficits, HRQoL was affected by stroke severity, comorbidities and age. Feelings of depression before ICH had stronger influence on reporting depression/anxiety after ICH than stroke severity‐related and outcome parameters. Thus, simple questions on patient's premorbid feelings of sadness/depression could be used to identify patients at risk of depression after ICH for focusing follow‐up and treatment.